Diversity in Germplasm of Pongamia pinnata (L.) Pierre and Its Traditional Uses in Southern Parts of Andhra Pradesh - Pandravada, S.R.; Joseph, B.; Sivaraj, N.; Varaprasad, K.S.; Kamala, V. (Indian Journal of Agroforestry, 2020)
An exploration was organized in southern parts of Andhra Pradesh in the districts of Mahaboobnagar, Kurnool, Cuddapah and Chittoor primarily to collect, conserve and evaluate the potential of Pongamia pinnata (L.) Pierre germplasm which resulted in acquiring 31 accessions. A data sheet specially developed for recording passport information has been enlisted. The frequencies for different descriptors and descriptor states, range of variability for pod and seed characters and promising accessions identified are highlighted. Traditional uses of Pongamia pinnata that are in vogue in the surveyed region are also presented in this paper.